Vincent's colors - Gogh, Vincent van, 1853-1890.; Lach, William, 1968-; Metropolitan Museum of Art (New York, N.Y.) (New York : Metropolitan Museum of Art ; San Francisco : Chronicle Books, 2005)
Vincent van Gogh corresponds with his younger brother, Theo, about his paintings.
Keywords: Gogh, Vincent van, -- 1853-1890 -- Correspondence -- Juvenile literature; Gogh, Theo van, -- 1857-1891 -- Correspondence -- Juvenile literature; Painters -- Netherlands -- Correspondence -- Juvenile literature; Color in art -- Juvenile literature; Picture books for children -- Juvenile literature